2018
DOI: 10.1177/1934578x1801300428
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical and Pharmacological Review on Cynomorium songaricum as Functional and Medicinal Food

Abstract: Cynomorium songaricum Rupr. (CSR) has a long history of being widely used as a functional food and medicine by different ethnic groups worldwide; CSR is used to treat impotence and premature ejaculation and traditionally used as natural source of tonic food. Numerous bioactive compounds linked with human health were recently identified. In this work, all available information on CSR were retrieved from NCBI PubMed and CNKI database, and the recent findings about the compositions and functions of CSR were summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…To date, the understanding of secondary metabolites of interest in C. songaricum is still limited, only 78 compounds have been isolated and identified, belonging to flavonoids, terpenoids, steroids, organic acids, and phloroglucinol adducts. 11 Although some of these compounds exhibit some pharmacological activity, they do not achieve all the pharmacological activity exhibited by the whole plant. 12 Studies have shown that each plant is composed of thousands of compounds, and many yet undefined compounds with trace amounts also influence the overall pharmacological activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, the understanding of secondary metabolites of interest in C. songaricum is still limited, only 78 compounds have been isolated and identified, belonging to flavonoids, terpenoids, steroids, organic acids, and phloroglucinol adducts. 11 Although some of these compounds exhibit some pharmacological activity, they do not achieve all the pharmacological activity exhibited by the whole plant. 12 Studies have shown that each plant is composed of thousands of compounds, and many yet undefined compounds with trace amounts also influence the overall pharmacological activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on the fundamental theories of the Traditional Mongolian Medicine, the therapeutic effects of GOYO-11 formulation, which is mainly formulated by Cynomorium songaricum according to the traditional pharmaceutical theory and techniques, has been studied in the process of the treatment of gastric ulcer. Cuiet et al [8] found that the Cynomorium songaricum protected the gastric mucosa against different ulcer-mimicking induction models (ethanol, NSAIDs, stress and pyloric ligation) through multiple mechanisms of action, such as cytoprotection, antioxidants. The present study demonstrated the gastroprotective effect of three different doses of GOYO-11 on aspirin-induced gastric ulcers in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Many components have been isolated from C.Songaricum and identi ed. Cuiet et al found that the signi cant constituents in medicinal preparations of C.Songaricum are avonoids, terpenoids, steroids, organic acids, polysaccharides, saccharides, and glycosides and phloroglucinol adducts [8]. The pharmacological properties of C.Songaricum include improved kidney function, clearing free radicals, anti-aging, anti-oxidation, anti-fatigue, and anti-anoxia, anti-stress, anti-HIV activities, stimulating immunologic functions, enhancing sexual functions and others.…”
Section: Introductionmentioning
confidence: 99%
“…The novel antibiotics and correlated chemotherapeutic agents' research are elevating and enriching the chemistry of medicinal plants (33,34). Medicinal plants are a dominant origin of antioxidants (35). The discovery of different natural antioxidants from plant sources heightens the antioxidant amplitude of the blood and leads to the depletion of the perils from certain infections (36,37).…”
Section: Screening Of the Antibacterial Activity By Micro Broth Dilution Assaymentioning
confidence: 99%